The Implementation of Passive Leg Raising in Shocked Patients: Scoping Review - Verawaty, Rotua Rina; Kosasih, Cecep Eli; Mirwanti, Ristina (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
Shock is a life-threatening condition. It is essential to perform hemodynamic support on shocked patients to restore adequate circulation. Passive leg raising (PLR) is a critical act to assess fluid responsiveness which can provide significant information about fluid needs of shocked patients. The present study aimed to identify the implementation of passive leg raising in shocked patients. The scoping review was the method used in the present study. Relevant literatures were obtained from PubMed, CINAHL and Google Scholar Search engines from 2013 to 2023. The articles were manually extracted through tabulation and the data were thematically analyzed with an exploratory descriptive approach. Nine articles were found relevant and hence were included in the present study. The findings of the 9 articles revealed that the implementation of passive leg raising in shocked patients was an early strategy in assessing fluid responsiveness and fluid administration could be decreased after 48 hours of ICU admission. The findings of the current study suggested that the implementation of PLR significantly assessed fluid responsiveness which in the end guided in conducting fluid resuscitation in shocked patients and could reduce fluid administration in shocked patients for the first 48 hours of ICU admission. Therefore, health professionals working in critical care units including critical care nurses should consider performing PLR to shocked patients.